Examining congruence in parent–teacher perceptions of middle school supports for students and families. Issue 6 (10th March 2021) - Garbacz, S. Andrew; Santiago, Rachel T.; Kosty, Derek; Zahn, Miranda; Stormshak, Elizabeth A.; Smolkowski, Keith; Seeley, John R.
Abstract: The purpose of this study was to examine parent–teacher congruent perceptions of middle school structures to support parent monitoring of children's behavior. We examined family educational involvement and school's communication and support to families as predictors of congruence, as well as congruence as a predictor of children following school rules and expectations. Participants were 415 teachers and 5003 parents across 40 public middle schools in the northwest region of the United States. Mixed‐effects regression was used to examine the cross‐sectional data. School size and student eligibility of free or reduced price school lunch were included as school‐level covariates. Results suggested that higher levels of teacher‐reported family involvement and school communication and support to families were significantly associated with greater parent–teacher congruence. In addition, results suggested that greater parent–teacher congruence was significantly associated with higher levels of teacher‐report of children following school rules and expectations. Implications for research on parent–teacher congruence and family–school collaboration are discussed at the school system level in terms of parent monitoring of children's behavior. Practical applications are reviewed for public middle schools.